Development and Scaling of Sustainable Feeds for Resilient Aquatic Food Systems in Sub-Saharan Africa: A systems theory of change - Manyise, Timothy; Kangogo, Daniel; Mutanuka, Evans; Adeosun, Festus; Akuwa, Elizabeth; Tanga, Chrysantus M.; Obeta, Charity; Jere, Arthertone; Siriwardena, Sunil; Yossa, Rodrigue; Rossignoli, Cristiano (WorldFish, 2023)
To understand the aquatic feed sector in Zambia, Kenya and Nigeria and to inform subsequent impact assessments of the Norad-Fasa project, the monitoring, evaluation, learning and impact assessment (MELIA) unit at WorldFish, together with implementing partners, organized 2-day workshops across the three countries. Using a participatory systems approach, the workshops brought together representatives of governments, nongovernmental organizations (NGOs), the private sector and farmers associations, as well as small-scale feed millers, fish aggregators, processors and smallholder fish farmers, to explore the potential socioeconomic impact of developing and scaling sustainable resilient feeds using local ingredients. The participatory systems approach is an emerging methodology that uses the lens of systems thinking to revolutionize impact assessment of projects by considering how they interplay with the environment that each project is embedded in.